2018
DOI: 10.1186/s40662-018-0095-0
|View full text |Cite
|
Sign up to set email alerts
|

Fundamentals of Presbyopia: visual processing and binocularity in its transformation

Abstract: BackgroundThe accommodation has considerable interactions with the pupil response, vergence response and binocularity. The transformation of visual reception processing and the changes of the binocular cooperation during the presbyopia development are still poorly studied. So, the regularities of visual system violation in the presbyopia formation need to be characterized. This study aims to reveal the transformation of visual reception processing and to determine the role of disturbances in binocular interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…The questionnaire on anamnesis, occupational information, and history of exposure to VTD was developed to collect information about the sociodemographic variables (sex and age), ocular history (ophthalmic or contact lens use, previous eye diseases, ocular treatment, and/or ocular surgeries), job characteristics (hospital, occupational groups, work schedules, and seniority), history of exposure to VDTs at work (hours per day of use), opinions about the ease of use of the software applications, and exposure to VDTs outside of work. Age was categorized as ≤35, 36–45, and >45 years, since each of these groups have different accommodative conditions (Girum et al, 2017; Rozanova et al, 2018). Seniority was categorized as ≤10, 10–20, and >20 years because these cut‐off points divided the sample into three groups of similar sizes.…”
Section: The Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The questionnaire on anamnesis, occupational information, and history of exposure to VTD was developed to collect information about the sociodemographic variables (sex and age), ocular history (ophthalmic or contact lens use, previous eye diseases, ocular treatment, and/or ocular surgeries), job characteristics (hospital, occupational groups, work schedules, and seniority), history of exposure to VDTs at work (hours per day of use), opinions about the ease of use of the software applications, and exposure to VDTs outside of work. Age was categorized as ≤35, 36–45, and >45 years, since each of these groups have different accommodative conditions (Girum et al, 2017; Rozanova et al, 2018). Seniority was categorized as ≤10, 10–20, and >20 years because these cut‐off points divided the sample into three groups of similar sizes.…”
Section: The Studymentioning
confidence: 99%
“…Age was categorized as ≤35, 36-45, and >45 years, since each of these groups have different accommodative conditions (Girum et al, 2017;Rozanova et al, 2018). Seniority was categorized as ≤10, 10-20, and >20 years because these cut-off points divided the sample into three groups of similar sizes.…”
Section: Data Collectionmentioning
confidence: 99%
“…Rabichev (1998) showed that the virtual binocular image obtained with a binarimeter is a measure of binocular interaction. Later, the method of spatial reconstruction of the area of binocular interaction (ABI), which enables calculation of the area of fusional field, was proposed [21,22], but the normative database of ABI under free haploscopy in non-strabismus patients is absent.…”
Section: Introductionmentioning
confidence: 99%